How do you convert p(x) = -8x^2 - 64x to vertex form?

I know the answer is p(x) = -8(x + 4)^2 + 128, but I'm unaware of the steps taken to get to that stage.

Any help is appreciated, thanks!

Respuesta :

Answer:

[tex]p(x)=-8(x+4)^2+128[/tex]

Step-by-step explanation:

Given, [tex]p(x)=-8x^2-64x[/tex]

Take -8 factor common,

[tex]p(x)=-8(x^2+8x)[/tex]

which can be written as

[tex]p(x)=-8(x^2+2 \times 4x)[/tex]

Add and subtract by 16 inside bracket,

[tex]p(x)=-8(x^2+2 \times 4x+16-16)[/tex]

[tex]p(x)=-8((x^2+2 \times 4x+4^2)-16)[/tex]

[tex]p(x)=-8((x+4)^2-16)[/tex]

[tex]p(x)=-8(x+4)^2+8 \times 16[/tex]

[tex]p(x)=-8(x+4)^2+128[/tex]